The haunting of room 904 : a novel - Wurth, Erika T. (Flatiron Books, 2025)
"From the author of White Horse ("Twisty and electric." -The New York Times Book Review) comes a terrifying and resonant novel about a woman who uses her unique gift to learn the truth about her sister's death. Olivia Becente was never supposed to have the gift. The ability to commune with the dead was the specialty of her sister, Naiche. But when Naiche dies unexpectedly and under strange circumstances, somehow Olivia suddenly can't stop seeing and hearing from spirits. A few years later, she's the most in-demand paranormal investigator in Denver. She's good at her job, but the loss of Naiche haunts her. That's when she hears from the Brown Palace, a landmark Denver hotel. The owner can't explain it, but every few years, a girl is found dead in room 904, no matter what room she checked into the night before. As Olivia tries to understand these disturbing deaths, the past and the present collide as Olivia's investigation forces her to confront a mysterious and possibly dangerous cult, a vindictive journalist, betrayal by her friends, and shocking revelations about her sister's secret life. The Haunting of Room 904 is a paranormal thriller that is as edgy as it is heartfelt and simmers with intensity and longing. Erika T. Wurth lives up to her reputation as "a gritty new punkish outsider voice in American horror.""--